UMA ANÁLISE DOS CONSELHOS MUNICIPAIS DE SAÚDE NA REGIÃO FRONTEIRA NOROESTE/RS - BOELTER, TAÍSA; FRAGA, CRISTINA K.; ROTTA, EDEMAR; PREUSS, LISLEI T.; AMES, MARIA A. C. (Salão do Conhecimento, 2013)
Resumo